COVID-19 Led to an Increased Online Search Interest for “Urticaria” - Malgotra, Vikas; Sharma, Sunakshi; Kaur, Jaspreet (Scripta Medica, 2024)
Background/Aim: Google Trends is a powerful tool for health information access and disease surveillance, including COVID-19 data forecasting. Cutaneous manifestations of COVID-19 include urticarial rash, which is multifactorial and may indicate a better prognosis. Aim of this study was to analyse the search queries for the term “urticaria” during the six years period (2017-2022) and assess the relationship between relative search volume (RSV) and a global rise in COVID-19 cases.Methods: This study examined search queries for "urticaria" from 2017 to 2022, exploring the relationship between RSV and global COVID-19 cases. Data on "urticaria" search volume in various countries were collected using Google Trends. Microsoft Excel and correlation analysis were used to analyse the data and investigate the association between search volume and monthly COVID-19 case rise.Results: During 2017-2019, the mean RSV for "urticaria" was 69.9 ± 10.1, which increased to 84.1 ± 8.6 during 2020-2022. The difference in means was statistically significant (p < 0.001). The mean RSV in 2022 (94.3) was the highest among all years studied. The increase in RSV from 2020 to 2022 moderately correlated (r = 0.56) with monthly COVID-19 case rise (p < 0.001). Nicaragua showed the highest search interest, while Africa, North America, Asia and Pacific, the Middle East and Europe had low search interest.Conclusions: This study identified a significant increase in search volume for "urticaria" during the COVID-19 pandemic. Nicaragua had the highest search interest, while English-speaking countries displayed low interest. Language variation, cultural differences and COVID-19-related health concerns may influence public interest in urticaria. These findings can aid public health officials in understanding public health concerns and tailoring effective health communication strategies.